2015
DOI: 10.5137/1019-5149.jtn.10800-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stem cell marker nestin and microrna-21 in meningiomas

Abstract: AIm: Meningiomas are one of the most common benign intracranial tumors, making up nearly one third of all primary intracranial tumors. The majority of meningiomas have benign histological features and total resection is associated with favourable prognosis. Atypical and malignant meningiomas are associated with increased risk of recurrence. In the present study we set out to investigate the role of nestin mRNA levels and miR-21 in meningiomas. mATeRIAL and meTHods:We studied 17 patients with meningiomas that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Nestin is a class six intermediate filament protein expressed in neural stem cells and BTSCs. Galani et al investigated the expression of Nestin in 17 patients with meningiomas using qRT-PCR and found that Nestin was expressed at higher levels in atypical and anaplastic meningiomas than in benign meningiomas (9). In the present study, all atypical and anaplastic meningiomas as well as the majority of benign meningiomas were positive for Nestin.…”
Section: █ Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Nestin is a class six intermediate filament protein expressed in neural stem cells and BTSCs. Galani et al investigated the expression of Nestin in 17 patients with meningiomas using qRT-PCR and found that Nestin was expressed at higher levels in atypical and anaplastic meningiomas than in benign meningiomas (9). In the present study, all atypical and anaplastic meningiomas as well as the majority of benign meningiomas were positive for Nestin.…”
Section: █ Discussionsupporting
confidence: 60%
“…Benign meningiomas are often treated with good results, but recurrence is very common among most malignant meningiomas. Moreover, some benign meningiomas can recur even after total resection and excision of the dura and affected bone (9). Therefore, we presume that meningioma tumor stem cells may be responsible for these events.…”
Section: █ Discussionmentioning
confidence: 97%
“…Up to 5 of 10 µm FFPE tissue sections were gathered according to the standard method 18 and were used for Equal quantity of DNA template of each sample was used in each 20 µL of reaction volume with 0.2 µM and 2.5 mM final primer and MgCl 2 concentration, respectively. Cycling conditions were set as follows (Table 2): pre-incubation/denaturation of secondary structures 10 min at 95°C, followed by 55 amplification cycles comprising 1 min denaturation at 95°C, followed by 60-s primer annealing T (according to each primer), and a 60-s elongation period at 72°C.…”
Section: Dna Extractionmentioning
confidence: 99%
“…The aberrant expression of OATP1B3 in the cytoplasm of colon tumors was the impetus to investigate whether OATP1B3 functions differently in the setting of malignancy. 8,10 The SLCO1B3 gene sequence (encoding OATP1B3) was shown to vary among different populations, as well as several single nucleotide polymorphisms (SNPs) were reported to date, [16][17][18][19][20][21] therefore the significance of SLCO1B3 polymorphisms on drug pharmacokinetics is becoming increasingly evident and the inter-ethnic differences exist in the allelic frequency of these variants suggests the need to characterize the full extent of SLCO1B3 genetic variability in any given population. 17 The study of polymorphisms of SLCO1B3 gene presents a special interest as they seem to be implicated in the function of the protein and promises a possible discrimination among patients in order to achieve personalized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The current research focus is the isolation and the characterization of the molecular profile of these CSCs, as much as the arachnoid is made up of a heterogeneous cell population, containing meningothelial, fibroblastic and endothelial cells, but also some cells associated to arachnoid-dura interface. Up to now, results are supporting the possibility of such a CSC occurrence in meningeal tumors, expressing characteristic markers, such as CD133, c-Myc, KLF4, NANOG, nestin, OCT4, SOX2, and vimentin [74][75][76]. Furthermore, several pathways characteristically involved in stem-cell signaling, belonging to Fibroblast Growth Factor (FGF), Hedgehog, Transforming growth factorβ/Bone Morphogenetic Protein (TGFβ/BMP), or Wnt are responsible for the maintenance of CSCs and pluripotent stem cells balanced values [77].…”
Section: Genetic Mutations In Meningiomas and The Signaling Pathways mentioning
confidence: 66%